Changes of Köppen–Trewartha climate types in the Tibetan Plateau during the mid-Holocene, present-day, and the future based on high-resolution datasets - Huang, Lingxin; Feng, Song; Chen, Jie; Deng, Yajie; Chen, Fahu; Huang, Wei (Frontiers in Earth Science, 2023)
Tibetan Plateau (TP) is strongly impacted by accelerated anthropogenic warming that already exceeds natural variability. However, the spatial differences in climate and ecosystem response in the TP between anthropogenic and natural forcings are unclear. Here, the Köppen–Trewartha climate classification is applied to examine the shifts in terrestrial climate regimes and vegetation distribution in the TP by analyzing the WorldClim high-resolution downscaled climate dataset for the mid-Holocene (MH, ~6 cal ka BP), the present-day (PD, 1960–1990), and in the future (2050) under the Representative Concentration Pathway (RCP) 4.5 and RCP8.5 scenarios. The results show that the polar climate and the dry climate occupied more than 70% of the TP area in the three periods. The MH, dominated by the natural forcing, is featured as having less distribution of dry climate than the PD. The anthropogenic change will promote a transition from a cold climate type to a warmer climate type in the 2050. The precipitation change is responsible for the differences in climate types between the MH and PD, while warming dominates the evolution of climate types across the TP in the 2050. Moreover, vegetation types can be represented by major climate types in a large proportion of TP. In particular, polar climate regions correspond well to the areas of meadows, and the dry climate regions correspond to the steppes and deserts areas. The large changes in the climate regimes of the TP suggest an extensive (shrinking) area of meadows (steppes) under natural forcing and a shrinking area of meadows under anthropogenic warming.